Pengaruh Informasi Asimetri dan Disclosure terhadap Cost of Capital - Aida Ainul Mardiyah (The Indonesian Journal of Accounting Research, 2013)
This study intends to identify the interactive effect of asymmetry information and disclosure on cost of capital. Data is selected using stratified random sampling. The analysis units are 72 companies registered on the Jakarta Stock Exchange in 1996. The data collection  is performed using archival. The statistic method used to test the hypotheses, are multiple regression, multiplicative model and nonmonotonic effect. In addition, an analytical method of utilizing partial derivative to test the contingency relationship as advocated by Waterhouse dan Tiessen (1978); Schoonhoven (1978); Govindarajan (1986); Chia (1995); Fisher  (1996); Botosan (1997), Nazaruddin (1998), and Mardiyah and Gudono (2001) is also used.The study results are as follows: first, The results provide support for the hypothesis that assymetry information and disclosure have an interactive effect on cost of capital. More specifically, the results show that disclosure significantly moderates the relationship between asymmetry information and cost of capital. The greater the degree of disclosure, the stronger the effect of low assymetry information on low cost of capital. Second, there are no differences among the available industries (i.e., service, manufacturing, and trading industries).